Chinese cyber security (قضايا سياسية, 2022)
The issue of cyber security has emerged as one of the most important precautions against political and economic conflicts between countries as a result of electronic or cyber wars that target infrastructure, facilities, government institutions, industrial networks and research and are in one way or another able to disrupt the operation of vital infrastructure, and in this regard, China had many motives for force. Cyber ​​and its enhancement, including political, economic, military, and security, as China is the first country to add a sovereign character to cyber because it imposed absolute control on the part of the state and became subject to the so-called (Great Firewall) with extensive cooperation with countries in this regard.